Prototipe Kursi Roda Elektrik dengan Kendali Joystick dan Smartphone - Junior, Andy Sadewa; Arifin, Fatchul (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
Wheelchairs are one of the walking aids for people with disabilities and also for people who are unable to move from one place to another. The purpose of this research was to build hardware and software into a wheelchair prototype that can be controlled with joysticks and smartphones and to know its performance. The method in making the final project consists of the stages of need identification, requirements analysis, system design, tool making, tool testing and data collection. Based on the testing that has been done, the results are obtained that the control input from the smartphone through the application and also the joystick produces the output of the wheelchair prototype movement according to the instructions that have been set as input. The maximum distance of the control system from the smartphone is 0-10 meters either with obstacles or without obstacles. The response of the wheelchair prototype device has an average error of 0.024. Smartphone applications that are used as controls can be installed on the latest Android version